Agama dan Kehidupan Manusia - ramli, ramli (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
This writing analyzes that religion has some roles in human life. In the research of community, religion considered as an element of culture, which is not neglected to be studied. In some way, religion is believed frequently as the source of comprehensive values that cover even inspire derivative values which is developed in human life. In observation, practical religion in society is also developed from religion doctrines and adjusted with the cultural environment. The concourse of doctrines and cultures seems obviously in the pratice of rituals, so religion and culture indeed united in the community. Therefore, religion has many roles in the human life and public sphere. However, in line with changes of the world, how does the religion role in the human life?